The possibilities of computer simulation of the orthognatic surgical procedure in the treatment of class II malocclusion - Milutinović Jovana; Nedeljković Nenad; Nikolić Predrag (Serbian Medical Society - Dental Section, Belgrade, 2008)
Aim: The aim of this study was to investigate the possibilities for computer-aided orthognathic surgery in the treatment of class II malocclusions. Materials and methods: Twelve patients treated at the Dept. of Orthodontics, School of Dentistry, Belgrade, were included in the study. Profile cephalometric analyses of all patients were conducted before and after the treatment. The first step was the profile cephalometric analysis before the treatment using the computer software Nemotec dental studio NX2005 and the second step was the computer-aided simulation using the same software. Results: The difference in the results was found in the soft-tissue analysis, which can be explained by the possibility of observing the instant changes in patients' profiles during the simulation of surgical treatment. Conclusion: Based on the results of the present study, it can be concluded that the computer-aided simulation provides a faster approach, a possibility to educate patients before the surgical treatment and a better clinician-patient communication.